TIME MANAGEMENT AND JOB PERFORMANCE: A QUALITATIVE ANALYSIS FROM ISLAMIC PERSPECTIVE - Rafikul Islam; Md. Yousuf Ali; Noor Mohammad Osmani (Journal of Islamic Management Studies, 2021)
Time is an important “amanah” or trust bestowed from Allah (swt) to human beings. Everybody has a fixed amount of time in this world. Utmost care should be taken and befitting attempts should be made to use time as it is meant to be. But then how to optimally use time? From the Islamic perspective, are there effective guidelines for the usage of time? Furthermore, does Islam teach us how to enhance our job performance by capitalizing time? In short, this study aims to answer these pertinent questions. This is done via face-to-face interview sessions involving ten selected Muslim interviewees with PhDs and those having at least five years of teaching experience. The responses were analyzed using a qualitative thematic approach. The analysis is based on the rich opinion data from the interviewees and the findings are rooted on Islamic principles. The study found that a Muslim’s time management starts by offering salats at their designated times. The interviewees recommended to set priorities on the task based on importance, have proper schedule, and meet deadlines. The study also found that good time management enhances job performance. From literature, though research on time management from the conventional perspective is abundant, studies in this area especially from the Islamic perspective is rather scanty. Consequently, the present research could be considered as an exploratory one. The paper finally recommends that further researches could be undertaken on similar topics and highlights certain avenues that could be pursued quantitatively.